Cross-country study. Economic policy challenges in the Baltics: rebalancing in an uncertain environment (Luxembourg, 2010)
"The study reviews the process of economic transformation in Estonia, Latvia and Lithuania from the early years of these countries' regained independence to the current downturn. In particular, the study examines macroeconomic and budgetary developments and policy, real and financial integration with the rest of the EU and medium-term challenges to optimise growth prospects. The emphasis lies on inferring policy lessons for small open economies undergoing rapid real and financial convergence, including the positive contribution which pursuing prudent policies over the medium term can make, also at a time of a crisis. "